INDEPENDENSI PERADILAN MILITER TERHADAP PRAJURIT TNI SEBAGAI PELAKU TINDAK PIDANA NARKOTIKA - Auliajr Aulia Jihan Rifani; Satria Unggul Wicaksana Prakasa (Universitas Muhammadiyah Malang, 2021)
Narcotics can be categorized into extraordinary crimes. Currently, the circulation of narcotics has targeted almost all circles. Military institutions are also not spared from the circulation of narcotics. The basic question is how to handle narcotics crimes by the Military judiciary and the legal efforts that can be made by the soldiers who are accused. The research method used is socio-legal legal studies: Data sources come from secondary data sources or literature studies, which review data from laws and regulations, readings, and books related to research titles. The settlement of narcotics crimes involving TNI soldiers is carried out by the military judiciary. The component or sub-system of military justice is the same as the general judiciary, namely the existence of Ankum and Papera which are important components in the military justice system, in addition to the Military Police, Oditur, and Military Judges. Soldiers involved in such crimes can also make legal efforts as a form of self-defense. The Military Judiciary has the authority to resolve its cases without interference from other agencies, as whose authority and position are contained in Law No. 31 of 1997